2015
DOI: 10.1037/a0038380
|View full text |Cite
|
Sign up to set email alerts
|

Exploring qualitative training reactions: Individual and contextual influences on trainee commenting.

Abstract: Training reactions are the most common criteria used for training evaluation, and reaction measures often include opportunities for trainees to provide qualitative responses. Despite being widely used, qualitative training reactions are poorly understood. Recent trends suggest commenting is ubiquitous (e.g., tweets, texting, Facebook posts) and points to a currently untapped resource for understanding training reactions. In order to enhance the interpretation and use of this rich data source, this study explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 81 publications
1
17
0
2
Order By: Relevance
“…To this end, researchers may consider increasing rapport with their respondents by displaying a video clip of researchers reading the survey instructions (Ward, Meade, Gasperson, & Pond, ), issuing a benign note about the existence of IER detection tools (Huang et al, ), and creating a tie between participant incentives and data quality (see Huang et al, ). As noted, researchers have found that participants are more likely to provide comments when they have an interest in the topic (Harman et al, )—interest may not be able to be manipulated by researchers, but providing some information on the survey topic and the projected use of the response data may help. Future research in this area should include interventions to reduce IER in online surveys, such as real‐time feedback in online surveys for individuals who fail more than one IER item or go through survey pages in an unlikely rapid fashion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, researchers may consider increasing rapport with their respondents by displaying a video clip of researchers reading the survey instructions (Ward, Meade, Gasperson, & Pond, ), issuing a benign note about the existence of IER detection tools (Huang et al, ), and creating a tie between participant incentives and data quality (see Huang et al, ). As noted, researchers have found that participants are more likely to provide comments when they have an interest in the topic (Harman et al, )—interest may not be able to be manipulated by researchers, but providing some information on the survey topic and the projected use of the response data may help. Future research in this area should include interventions to reduce IER in online surveys, such as real‐time feedback in online surveys for individuals who fail more than one IER item or go through survey pages in an unlikely rapid fashion.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, more satisfied groups are more likely to respond to organisational surveys. Also, Harman et al () found that participants in a training program were more likely to provide comments (training reactions) when they had an interest in the topic. We speculate that this could extend to individuals having an interest in the survey topic being more likely to pay attention to items and display lower levels of IER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No contexto da EAD a reação pode também ser avaliada qualitativamente, por meio de comentários em tweets, mensagens de texto e postagens no Facebook. A avaliação de reação qualitativa ainda é pouco explorada por estudos cintíficos, mas há evidências de que os comentários dos treinandos influenciam os comportamentos dos estudantes e isso pode predizer a aprendizagem e a efetividade do treinamento (Harman, Surface, Ellington, & Thompson, 2015).…”
Section: Reaçãounclassified
“…Research utilizing MLMs are common in IO psychology. A review of recent articles (2012late spring of 2015) in The Journal of Applied Psychology, The Academy of Management Journal, and Personnel Psychology (see Table 1) reveals studies across a wide variety of subjects, including creativity (e.g., Chang, Jia, Takeuchi, & Cai, 2014;Hirst, Van Knippenberg, Zhou, Quintane, & Zhu, 2015), training reactions (e.g., Harman, Ellington, Surface, & Thompson, 2014), culture and commitment (e.g., Fisher, 2014), groups and teams (e.g., Chang et al, 2014;Farmer, Van Dyne, & Kamdar, 2015;Gonzalez-Mule, DeGreest, McCormick, Seong, & Brown, 2014) and leadership (e.g., Chen, Zhu, & Zhou, 2015;Dong, Liao, Chuang, Zhou & Campbell, 2015;Farh & Chen, 2014;Liu, Wang, Chang, Shi, Zhou, & Shao, 2014).…”
Section: Mlms In Iomentioning
confidence: 99%